Due Process and Criminal Law Cases with Special Regard to Central Europe - Crişan , Eugen-Gheorghe (The ECHR at 70: The Central European Narrative, 2025)
The right to a fair trial is probably the most comprehensive and complex of the rights provided for in the European Convention on Human Rights (ECHR, or ‘convention’). This, in order to be respected as a whole, requires respect for the other rights which compose it – and which in turn are composed of other requirements, conditions and elements – each of which in turn must themselves be respected. The European Court of Human Rights (ECtHR or ‘court’), which is constantly confronted with new situations arising in the national practice of EU member states, constantly consolidates or reinforces its case law on each element of the right to a fair trial, thus ensuring that the authorities of the member states – whether political, judicial or otherwise – act accordingly. In order to ensure that the legal provisions contained in Article 6 of the convention and the case law of the court are complied with as faithfully as possible, it is useful to be familiar with all the case law, irrespective of which European state it refers to and whether it is older or more recent, since only a cross-referencing of all of them offers the ideal way forward. It could be said that the judicial systems of the countries located in Central and Eastern Europe offer the most negative cases, but this is not really the case: there are plenty of such cases in other more ‘modern’, evolved systems – towards which those of the countries located in this part of Europe tend – and their progress in this respect is notable, which is gradually leading to a visible decrease in the number of such cases. The fact is that the direction in which things are going is largely due to the court, which, in each case decided, sets benchmarks between which national legislation and judicial practice must fall.Keywords: criminal charge, independent and impartial court, fairness, publicity of trial, reasonable time, presumption of innocence, right of defence